Gastroesophageal reflux disease in bronchial asthma: What we need to know? - Patil,Shital; Gondhali,Gajanan V.; Choudhari,Shubham Radhesham (Global Journal of Health Sciences and Research)
Gastroesophageal reflux disease (GERD) is most common disease with variable presentation from asymptomatic to frank symptomatic disease having impact on various respiratory disease such as cough, bronchitis, bronchial asthma, chronic obstructive pulmonary disease, and interstitial lung diseases. GERD is defined by retrograde reflux of gastric contents to the esophagus leading to various signs and symptoms that range from heartburn/ regurgitation to the development of extraesophageal respiratory syndromes like asthma. Bronchial asthma and GERD are more common diseases and usually reported more frequently as “two side sides of same coin.” GERD has been associated with a causal link for asthma, worsening of asthma control, one of the causes for refractory asthma, and a main factor in asthma cases with recurrent asthma exacerbation. Asthma itself and medicines used for the treatment of asthma are associated with GERD, worsening of GERD and one of the causes for refractory GERD. However, asthmatics have been found to have a much greater prevalence of GERD symptoms than the general population. There remains debate regarding the underlying physiologic mechanism of this relationship and whether treatment of GERD actually translates into improved asthma outcomes. The clinical prevalence of the two conditions in many patients cannot be ignored, and multiple theories highlighting plausible pathogenic explanations for these associations have been described. The treatment of symptomatic GERD in patients with asthma is important to control the underlying GERD and should be undertaken based on current guidelines for the treatment of the GERD.